Significant clinical response of advanced colorectal cancer to combination therapy involving capecitabine and adoptive cell transfer therapy: a case report - Li, Shuchun; Ma, Junjun; Hong, Xizhou; Zheng, Minhua; Goto, Shigenori; Takimoto, Rishu; Kamigaki, Takashi; Zang, Lu (Translational Cancer Research, 2019)
Significant clinical response was obtained in a patient with stage IV colorectal cancer (CRC) following combination therapy involving capecitabine and adoptive cell transfer therapy. She had laparoscopic lower anterior resection and left liver metastatic carcinoma resecting in 20th, February, 2017. Capecitabine was used to further treatment for an unresectable hepatic metastasis. The serum level of carcinoembryonic antigen (CEA) was increased significantly after dropped temporarily. Since then, the patient took the adoptive cell transfer therapy at the same time. αβT cells and NK cells were injected intravenously into the patient. After the first transfusion with αβT cells, the tumor biomarker, CEA, dropped obviously from 14.7 to 6.1 ng/mL. And it came to 1.9 ng/mL after four times treatment, which was back into normal range (